2003
DOI: 10.1056/nejmoa035103
|View full text |Cite
|
Sign up to set email alerts
|

Structured Treatment Interruption in Patients with Multidrug-Resistant Human Immunodeficiency Virus

Abstract: In patients infected with multidrug-resistant HIV, structured interruption of treatment was associated with greater progression of disease and did not confer immunologic or virologic benefits or improve the overall quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
122
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(134 citation statements)
references
References 15 publications
(16 reference statements)
9
122
1
2
Order By: Relevance
“…6,7 Studies evaluating CD4-guided treatment interruption and structured treatment interruptions have had mixed results and have not demonstrated consistent benefits to subjects. [8][9][10][11][12][13] Results of studies of short-cycle therapy, the interruption of therapy for 2 to 7 days only, have demonstrated mixed results. Dybul and colleagues demonstrated good initial results of a study in adults of 7 days on=7 days off therapy with sustained viral control and stable CD4 þ T cell counts.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Studies evaluating CD4-guided treatment interruption and structured treatment interruptions have had mixed results and have not demonstrated consistent benefits to subjects. [8][9][10][11][12][13] Results of studies of short-cycle therapy, the interruption of therapy for 2 to 7 days only, have demonstrated mixed results. Dybul and colleagues demonstrated good initial results of a study in adults of 7 days on=7 days off therapy with sustained viral control and stable CD4 þ T cell counts.…”
Section: Introductionmentioning
confidence: 99%
“…Other options such as complete or partial structured treatment interruptions have failed to show consistent benefit or not undergone careful scrutiny in clinical trials. [22][23][24] Complicating these decisions is the relative paucity of data regarding the rate at which anti-retroviral resistance develops after the onset of virologic treatment failure in patients receiving highly active anti-retroviral therapy (HAART). [25][26][27] The purpose of this study was to define the time to accrual of genotypic resistance mutations, particularly thymidine analogue mutations (TAMs) and major protease inhibitor mutations, in persons with a persistently detectable plasma viral load (pVL) despite being on a stable antiretroviral regimen.…”
mentioning
confidence: 99%
“…On the other hand, it also has been shown that interruption of HAART can convert a resistant virus population to wild-type virus [24][25][26][27]. Although this strategy has been harmful in the patients receiving salvage therapy [28], the situation may be different in immunologically intact patients infected with HIV resistant to NRTIs but treated successfully with HAART. Indeed, major HIV mutations present after dual-NRTI therapy and before HAART had disappeared after STI.…”
Section: Discussionmentioning
confidence: 99%